Effect of ferulic acid derivative concentration on the release kinetics, antioxidant capacity, and thermal behaviour of different polymeric films. (1st June 2023) - Khan, Muhammad Rehan; Fadlallah, Sami; Gallos, Antoine; Flourat, Amandine L.; Torrieri, Elena; Allais, Florent
Highlights: The BDF displayed good stability with 86–93% retention in films. Release kinetics of BDF was influenced by polymer nature and BDF concentration. The BDF displayed faster DPPH reaction kinetics as compared to ferulic acid. BDF (>20 w%) led to crystallization due to a lack of interaction with PLA. Abstract: Ferulic acid displays poor thermal resistance during extrusion and compression moulding, slow 2, 2-diphenyl-1-picrylhydrazyl (DPPH) reaction kinetics, and undetected release from polylactide (PLA) and polyhydroxyalkanoates (PHA)-based films into polar media. Thus, in this study, a ferulic acid derivative Bis- O -dihydroferuloyl-1, 4-butanediol (BDF) was used as an active additive (up to 40 w%) in PLA, poly(3-hydroxybutyrate) (PHB), and poly(3-hydroxybutyrate- co -3-hydroxyvalerate) (PHBV) matrices to produce blends by extrusion. These blends were then used to prepare films by solvent casting. The BDF displayed good stability with 86–93% retention. The release kinetics in Food Simulant A revealed higher BDF release amounts (1.16–3.2%) for PHA-based films as compared to PLA. The BDF displayed faster DPPH reaction kinetics as compared to ferulic acid. The PHA-based films containing BDF displayed > 80% of DPPH inhibition. The growth of crystals inside polymer matrix had a nucleation effect which reduced the glass transition temperature of the films.